Expo Pendidikan: Pemanfaatan Aneka Buah sebagai Bahan Alternatif Fermentasi Wine Buah di Kecamatan So’a - Bao, Antonia Paulina; Limbu, Umbu N.; Neta, Agusto D.P.S. (Jurnal Pengabdian Masyarakat - PIMAS, 2025)
Through the distribution of resources and the display of finished goods, the education expo aims to increase community and student understanding. In the So'a District, students from STIPER Flores Bajawa's Applied Biology Study Program organized an event where they displayed goods made through fermentation processing, including fruit wine. Tropical fruits such tamarillos, bananas, watermelons, oranges, and others may be found in Ngada Regency. Usually, these fruits are eaten straight away without previously being turned into food or drink items. People in the area are used to drinking alcoholic drinks including wine, beer, and moke. Other tropical fruits can be used as the foundation for wine production in addition to grapes. The purpose of this community service project is to educate the locals on how to turn tropical fruits into economically valuable wine and beverage products. In order to make wine from tamarillo, banana, watermelon, and orange, demonstration and experimental approaches were employed. Visitors to the exhibition evaluated the fruit wines based on their color, flavor, and scent. The panelists favored tamarillo wine because of its appealing dark red color, aroma of fruit and alcohol, and more delectable taste brought on by the combination of these flavors.